Ruin problem for an inhomogeneous semicontinuous integer-valued process - Gusak, D. V.; Гусак, Д. В. (Institute of Mathematics, NAS of Ukraine, 2000)
For a process ξ(t = ξ1(t)+χ(t), t≥0, ξ(0) = 0, inhomogeneous with respect to time, we investigate the ruin problem associated with the corresponding random walk in a finite interval, (here, ξ1 (t) is a homogeneous Poisson process with positive integer-valued jumps and χ(t) is an inhomogeneous lower-semicontinuous process with integer-valued jumps ξ n ≥-1).